Pengaruh Pendapatan Pembiayaan Mudharabah, Musyarakah dan Murabahah Terhadap Pertumbuhan Laba Bersih (Studi Kasus KSPPS BMT UGT Nusantara Kantor Pusat Periode 2018-2021 - Halimah Halimah; Afi Rachmat Slamet; Restu Millaningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This research aims to determine the effect of Mudharabah, Musyarakah and Murabahah financing income on profit growth at KSPPS BMT UGT Nusanatar Head Office periose 2018-2021. The method used in this research is descriptive quantitative. The population of this study were all financial statements of KSPPS BMT UGT Nusantara Head Office 2018-2021. The sampling technique used saturated sampling, where the sample in this study consisted of 4 samples in the form of annual financial reports of KSPPS BMT UGT Nusantara Head Office 2018-2021. The data used in this study are secondary data. This data analysis uses multiple linear regression analysis. The results showed that Mudharabah financing income had a significant positive effect on net profit growth, Musyarakah financing income had a significant positive effect on net profit growth and Murabahah financing income had a significant positive effect on net profit growth. While simultaneously Mudharabah, Musyarakah, and Murabahah financing income affect net profit growth. Keywords: Mudharabah, Musyarakah, Murabahah financing income, net profit growth.